Implementation of Knowledge Management in Small and Medium Enterprises – Malaysian Perspective - Rehman, Mobashar; Mahmood, Ahmad Kamil; K. Sugathan, Savita; Amin, Aamir (2009)
Objective of the study was to have an insight about the situation of KM implementation in Malaysian Small and Medium Enterprises (SMEs). Study was conducted in Perak state of Malaysia. 30 SMEs were approached to participate in the study. SMEs were selected by using systematic random sampling. Critical Success Factors (CSFs) for the implementation of KM in SMEs were analyzed. Prioritized list of 14 CSFs was produced. Prioritization was done on the basis of R-square value (linear regression) and was cross checked by mean value. Beside these CSFs, types of KM applications used by Malaysian SMEs were also discussed. Current level of KM implementation by Malaysian SMEs was checked. Intention of Malaysian SMEs to implement KM in future, number of years KM has been implemented in Malaysian SMEs and projected duration other SMEs will take to implement KM were also among the topics discussed in the paper.